Artificial rearing of the peach fruit fly Bactrocera zonata (Diptera: Tephritidae). (28th August 2014) - Sookar, P.; Alleck, M.; Ahseek, N.; Permalloo, S.; Bhagwant, S; Chang, C.L.
Abstract : Integration of the sterile insect technique (SIT) into the area-wide management of the peach fruit fly Bactrocera zonata (Saunders) is a promising alternative to the localized use of chemical control tactics. Implementation of the SIT requires adequate numbers of sterile male insects that are produced in large mass-rearing facilities. The present study was carried out to improve the rearing methods of the peach fruit fly so as to contribute to the development of effective mass-rearing protocols. Commercially available papaya, mango, peach and guava juices were found to be equally effective as oviposition stimulants. Moreover, with respect to the fecundity and fertility of flies, water was found to be as effective as the tested fruit juices. During the first 3 weeks, 90% of the total eggs produced were collected from adult oviposition cages holding 50, 000 flies. A larval diet composed of sugarcane bagasse, ground maize, sugarcane sugar, waste brewer's yeast, wheat bran, benzoic acid, nipagin and water resulted in the following values for the quality control parameters: egg hatch 85%, pupal recovery >67%, pupal weight >4.2 g, pupation >95%, adult emergence >89%, and fliers >65%. Adult emergence and flight ability were similar for pupae placed in sand and vermiculite as the pupation medium.